A comparative laboratory analysis of fluoride content of dentifrices available in Metro Manila - Cuevas, Divina Socorro R.
The objectives of this study are to determine if there is a significant difference in the fluoride content of commercially available dentifrices, their stability within a certain period of time and to compare the computed total fluoride content of the samples and the standard agent concentration. Experiments were conducted on seven brands of commercially available dentifrices, five of which were locally manufactured and the other two toothpastes were imported samples bought from PX store. It was deduced from the experiments that different brands of tooth pastes have different amount of total fluoride contents which is one of the factors that affect the efficacy of the dentifrices. Visual examination of the extruded part of the dentifrice revealed that the contents have not been contaminated based from observations of no change in color. Its concluded therefore that there is a significant difference in the fluoride content of commercially available fluoride dentifrices which remains constant within three months. The total fluoride content of three out of seven tested dentifrices has at least 65% that of the dentifrices with standard agent concentration.